2021
DOI: 10.3390/ma14081855
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Mg-Mn-Zn Alloys for Medical Applications

Abstract: The magnesium alloys Mg-0.5Mn-2Zn, Mg-1.0Mn-2Zn, and Mg-1.5Mn-2Zn (wt.%) with potential biomedical applications, synthesized by powder metallurgy, were investigated to evaluate the influence of manganese content on their microstructure, mechanical properties, and corrosion resistance. The results show that Mg-Mn-Zn alloys prepared by powder metallurgy reached the maximum compressive stress of 316 MPa and the maximum bending strength of 186 MPa, showing their good resistance to compression and bending, and meet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…In accordance with the above observation, the biocorrosion process releases Zn ions into the cultured medium, impeding the proliferation of tumor cells by altering the cell cycle and inducing cell apoptosis through the activation of the mitochondrial membrane potential and caspase cell cycle [ 60 ]. Furthermore, Mn exhibits no toxic effect and plays a crucial role in activating various enzymes, such as hydrolases, kinases, transferases, decarboxylases, and mitochondrial respiration [ 61 , 62 ]. In conjunction with Mn and Zn, Mg also plays a significant role in suppressing tumor cells.…”
Section: Cytotoxicity Behavior Of Mg–mca Alloysmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with the above observation, the biocorrosion process releases Zn ions into the cultured medium, impeding the proliferation of tumor cells by altering the cell cycle and inducing cell apoptosis through the activation of the mitochondrial membrane potential and caspase cell cycle [ 60 ]. Furthermore, Mn exhibits no toxic effect and plays a crucial role in activating various enzymes, such as hydrolases, kinases, transferases, decarboxylases, and mitochondrial respiration [ 61 , 62 ]. In conjunction with Mn and Zn, Mg also plays a significant role in suppressing tumor cells.…”
Section: Cytotoxicity Behavior Of Mg–mca Alloysmentioning
confidence: 99%
“…The results indicated that the EW62 alloy displayed the best antitumor properties. Natalia Anisimova et al [ 61 ] studied the cytotoxicity of the biodegradable magnesium alloy WE43 in regard to tumor cells, such as LNCaP and MDA-MB-231 cells. The alloys were developed by using severe plastic deformation using the ECAP technique.…”
Section: Cytotoxicity Behavior Of Mg–mca Alloysmentioning
confidence: 99%
“…In recent years, a number of researchers [133][134][135][136][137][138][139] that produced Mg alloys used the Powder Metallurgy process route. This process is usually followed by extrusion to form the final alloy.…”
Section: Powder Metallurgymentioning
confidence: 99%
“…10 Therefore, the inclusion of alternative biocompatible alloying elements can provide a solution to these limitations. In this regard, various alloying components, including Zn, 11 Mn, 12 Zr, 13 Sn 14 and HA, 15 among others, have been added to magnesium in different weight ratios and combinations to overcome these limitations. Moreover, other studies have explored coating magnesium with these alloying elements as well as certain biopolymers to enhance its effectiveness across various applications, particularly in medicine.…”
Section: Introductionmentioning
confidence: 99%